Pengaruh Kepemimpinan, Komitmen Organisasi Dan Motivasi Kerja Terhadap Kinerja Pegawai BPKPD Kota Tebing Tinggi - Aisyah Siregar; Julianti Julianti; Khairunnisa Khairunnisa (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2026)
This researcher aims to determine the influence of leadership, organizational commitment anda work motivation on employee performance of BPKPD Tebing Tinggi City. This type of research is quantitative with a replication method where indicators, new research objects or analytical tools are the same as previous research. This study used a sample of 37 respondents. Sampling using saturated sample method. The data collection technique used is a questionnaire / questionnaire. The test equipment used is validity test, reliability test, coefficient of determination, linear regression and hypothesis testing using IBM SPSS 25 software. From the results of this test it can be concluded that there is an influence of leadershep (X1) on Employee Performance (Y) and there is an influence between organizational commitment (X2) on Employee Performance (Y) and that there is no influence between work motivation (X3) on Employee Performance (Y). Based on the research results, it can be seen that the value of the adjusted R square is 0.377 or 37,7%. This shows that if the Leadershep Variable (X1), Organizatinal Commitment Variable (X2) and Work Motivation Variable (X3) can explain the Employee Performance (Y) by 37,7%, the remaining 63,3% (100% - 37,7%) is explained by other variables that are not researched.